The Power of Symbolism in the Holy Qur’an: A Literary Analysis - Muslihed-Dien, Nassief; Salim Hameed, Fahmi (Opción, 2019)
The present paper aims at identifying the term symbolism, specifying some symbols manifested in the Holy Qur’an, presenting a literary analysis to the specified symbols, and highlighting the power of symbolism technique as a literary miraculousness of the Holy Qur’an in presenting vivid images. The significance of the present paper arises from the fact which says that the sym- bolism technique is used in the Holy Qur’an before more than 1400 years to present vivid sermonic and social lessons, whereas recently it has become an essential technique in modern writings in presenting social images. The signif- icance also came from that the paper intends to glorify the symbols used in the Holy Qur’an in presenting sermonic and lessons in the present life to preserve the moral and to get a reward in the life to come. The present paper follows the descriptive method in collecting and analyzing the data manifested in the Holy Qur’an. Due to the procedures, the paper arrives at certain findings. Depending on these findings, recommendations and suggestions are put forward.